2012
DOI: 10.1021/jp304770h
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Protein–CO2 Interactions as Elucidated via Molecular Dynamics

Abstract: Rising global temperatures require innovative measures to reduce atmospheric concentrations of CO(2). The most successful carbon capture technology on Earth is the enzymatic capture of CO(2) and its sequestration in the form of glucose. Efforts to improve upon or mimic this naturally occurring process will require a rich understanding of protein-CO(2) interactions. Toward that end, extensive all-atom molecular dynamics (MD) simulations were performed on the CO(2)-utilizing enzyme phosphoenolpyruvate carboxykin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 81 publications
(190 reference statements)
0
7
0
Order By: Relevance
“…On the basis of the nature of interactions of these (Arg, His, and Tyr) amino acids with CO 2 , these amino acids are called "CO 2 -philic" residues. 54 On the basis of mutation studies, Arg 92 was earlier proposed 19 to bind the substrate (oxalate); our results suggest that it can also bind the product CO 2 . The formate molecule was found to be bound to Arg 92 through strong hydrogen bonding interaction (see Figure S4 of the Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 55%
“…On the basis of the nature of interactions of these (Arg, His, and Tyr) amino acids with CO 2 , these amino acids are called "CO 2 -philic" residues. 54 On the basis of mutation studies, Arg 92 was earlier proposed 19 to bind the substrate (oxalate); our results suggest that it can also bind the product CO 2 . The formate molecule was found to be bound to Arg 92 through strong hydrogen bonding interaction (see Figure S4 of the Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 55%
“…[23][24][25] For instance, Rosi and coworkers 26 have studied the CO 2 uptake capacity of MOFs through the cation exchange method, in the presence of methylated onium ions operating via various noncovalent interactions. Interestingly Cundari et al [27][28][29][30][31] concluded that acid-base interactions are the principal chemical force by which CO 2 binds to proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Once identified the CO 2 binding site, the entry route for the substrate to the active site was also investigated by means of all-atom molecular dynamics (MD) simulations in explicit solvent. MD simulations have been widely used to investigate ligand migration paths inside proteins, also in the case of CO 2 ligand [39] , [40] , [41] but little is known on this topic for CAs, apart from few MD studies on hCA II isoform [42] , [43] , [44] . As first step, we employed CAVER program [33] to identify tunnels inside the protein, using the here reported X-ray structure of Zn-R3.…”
Section: Resultsmentioning
confidence: 99%